Recurrence for probabilistic extension of Dowling polynomials - Ma Yuankui; Kim Taekyun; Kim Dae San; Xu Rongrong (Open Mathematics)
Spivey found a remarkable recurrence relation for Bell numbers, which was generalized to that for Bell polynomials by Gould-Quaintance. The aim of this article is to generalize their recurrence relation for Bell polynomials to that for the probabilistic Dowling polynomials associated with YY and also that for the probabilistic rr-Dowling polynomials associated with YY. Here YY is a random variable whose moment generating function exists in a neighborhood of the origin.